Rewrite g(x) as x-1
------
4
and then substitute this result for x in f(x) = x^2 - 3x + 3:
f(g(x)) = (x-1)^2 / 4^2 - 3(x-1)/4 + 3.
At this point we can substitute the value 5 for x:
f(g(5)) = (5-1)^2 / 4^2 - 3(5-1)/4 + 3
= 16/16 - 3(4/4) + 3 = 1 - 3 + 3 = 1
Therefore, f(g(5)) = 1.
Answer:
V = 214.32
Step-by-step explanation:
Remark
You have to be a little careful with this question. The temptation is just to take the difference of the heights. That is not correct. The difference has to be multiplied by the base to get the volume.
Formula
V = (h1 - h2)* Base
Givens
h1 = 32.9
h2 = 29.1
Base = 56.4
Solution
V = 56.4 ( 32.9 - 29.2)
V = 56.4 * 3.8
V = 214.32
A vertical line i believe since x is constant